Enterprise Mac administrator's guide - Edge, Charles S.; Hunter, Beau.; Smith, Zach.; Safari eBooks ([New York] : Apress : Distributed to the book trade worldwide by Springer-Verlag New York, 2009)
"Charles Edge, Zack Smith, and Beau Hunter provide detailed explanations of the technology required for large-scale Mac OS X deployments and show you how to integrate it with other operating systems and applications"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Mac OS; Operating systems (Computers); Electronic books